Transmedia directors artistry, industry and new audiovisual aesthetics - Perrott, Lisa; Vernallis, Carol; Rogers, Holly (Professor of music) (New approaches to sound, music, and media, 2020)
A look at the signature styles of well-known film and music video directors such as David Lynch, Wes Anderson, and Baz Luhrmann in their relationship to sound, music, and image"--